The Jurisprudential Characterization of Appeal in the Interest of Law According to the Jordanian Code of Sharia Procedure No. (31) of 1959 and Its Amendments Until 2023 - Al-Abdallat, Idrees Ajaj Ahmad; Bani Salamah, Muhammad Khalf Muhammad (Journal of Islamic and Religious Studies, 2025)
This study aimed to examine the jurisprudential characterization of the appeal in the interest of law by the Jordanian Code of Sharia Procedure No. 31 of 1959 and its subsequent amendments up to the year 2023. Hence, the research aimed to expound on the definition of such an appeal, determine its jurisprudential classification, and delineate its legal and jurisprudential implications. The study employed the descriptive, analytical, and comparative methodologies. It found that the appeal in the interest of law constituted an exceptional legal mechanism intended to safeguard public order. Besides, it was found that the foundation of this legal remedy aligned with the Islamic jurisprudential concepts of accountability (hisbah) and public rights (al-ḥaqq al-‘ām). Moreover, the study highlighted that the provisions governing appeals in the interest of law did not apply to the actual litigants, but rather aimed to correct judicial interpretation and ensure consistency in judicial precedent. According to the findings, the study recommended the role of the Sharia Public Prosecution, clarifying the relationship between jurisprudence and statutory law, raising legal awareness, reviewing relevant legislative texts, and enhancing the function of the Sharia Supreme Court.